A D-optimal design to model the performances of dressings and devices for negative pressure wound therapy. Issue 2 (May 2016) - Salvo, P.; Smajda, R.; Dini, V.; Saxby, C.; Voirin, G.; Romanelli, M.; Di Francesco, F.
Abstract: A D-optimal design was used to identify and model variables that affect the transit time of wound exudate through an illustrative dressing used for negative pressure wound therapy. Many authors have addressed the clinical benefits of negative pressure wound therapy, but limited information is available on how to assess performances of dressings. In this paper, the transit time of wound exudate through a dressing was chosen as a model parameter to show how experimental design (DOE) can be used for this purpose. Results demonstrated that rate of exudate production, temperature and dressing thickness were the variables with the largest impact on transit time. The DOE approach could be used to model other dressing properties, like for example capability of absorbing excess exudate or breathability. Graphical abstract: Highlights: A chemometric approach to evaluate performances of wound dressings. A study of the exudate transit time through the dressings. An experimental set-up to simulate the exudate production at different rates.